Low temperature storage affects the ascorbic acid metabolism of cherry tomato fruits - Tsaniklidis, Georgios; Delis, Costas; Nikoloudakis, Nikolaos; Katinakis, Panagiotis; Aivalakis, Georgios (My University, 2014)
Tomato fruits are an important source of l-Ascorbic acid, which is an essential compound of human diet. The effect of the widespread practice of cold storing (5-10 °C) tomato fruits was monitored to determine its impact on the concentration and redox status of l-Ascorbic acid. Total l-Ascorbic acid levels were well maintained in both attached fruits and cold treated fruits, while in other treatments its levels were considerably reduced. However, low temperature storage conditions enhanced the expression of most genes coding for enzymes involved in l-Ascorbic acid biosynthesis and redox reactions. The findings suggest that the transcriptional up-regulation under chilling stress conditions of most genes coding for l-Ascorbic acid biosynthetic genes galactono-1,4-lactone dehydrogenase, GDP-d-mannose 3,5-epimerase but also for the isoenzymes of ascorbate peroxidase, monodehydroascorbate reductase, dehydroascorbate reductase enzyme, glutathione reductase that are strongly correlated to the l-Ascorbic redox status. Moreover, fruits stored at 10 °C exhibited higher levels of transcript accumulation of MDHAR2, DHAR1, DHAR2, GR1 and GR2 genes, pointing to a better ability to manage chilling stress in comparison to fruits stored at 5 °C.
Keywords: Ascorbic acid; Cherry tomatoes; Low temperature treatments; Transcriptional regulation; Vitamin C